Distribution of temperature in a quill cylinder made of visco-elastic material under the effect of vibratory load - G. B. Vermishyan (National Academy of Sciences of Armenia)
The distribution of temperature in a quill cylinder made of visko-elastic is examined, which inner and outer surfaces are under the effect of vibratory load. The problem is solved in two cases. In the first case the inner surface is heat insulated, and the temperature of the outer surface is equal to the ambient temperature. In the second case the inner surface is heat-insulated, and on the outer surface a free heat transfer into the surrounding medium takes place, which is conform to the Newton’s law. В работе рассматривается распределение температуры в полом цилиндре из вязкоупругого материала, когда на внутреннем и внешнем поверхностях действует вибрационная нагрузка. Задача решена для двух случаев. Первый случай, когда внутренняя поверхность теплоизолирована, а на внешней температура равна температуре окружающей среды. Во втором случае, когда внутренняя поверхность теплоизолирована, а на внешней происходит теплообмен с окружающей средой, подчиняющейся закону Ньютона.
Keywords: Science; Physics